Attitudes Towards Statistics in Secondary Education: Findings from fsQCA - Peiró-Signes, Ángel; Trull, Óscar; Segarra-Oña, Marival; García-Díaz, J. Carlos (Mathematics (Basel), 2020)
Students report a high degree of anxiety and reduced self-confidence when facing statistical subjects, especially in secondary education. This anxiety turns into poor academic performance. Most studies have used linear models for studying the interrelation between different attitudes and proving their impact on performance or related variables. This study uses a different approach to explain and better understand the causal patterns of factors stimulating lower levels of anxiety in students when facing statistics in secondary education. We employed the Multi-factorial Scale of Attitudes Toward Statistics (MSATS) and fuzzy-set qualitative comparative analysis (fsQCA) on a sample of 95 secondary school students in Spain. We identified the recipes or causal combination of factors, leading to low and high levels of anxiety. The results indicate that self-confidence and motivation are important factors in these recipes, but there is no single necessary condition that ensures lower levels of anxiety.